The Experiences of Three Teachers Using Body Biographies for Multimodal Literature Study - Morawski, Cynthia; Sokolowski, Jessica (International Journal for Talent Development and Creativity, 2023)
The body biography, a visual and written life-size composition to study characterization, makes use of a variety of materials such as markers, crayons, and found material from wrapping paper to remnants of string and yarn. In this study, three teachers were invited to implement the body biography practice as part of their delivery of the English curriculum to answer the question, “What are the experiences of three teachers who applied the body biography practice to teach literature in their English classrooms in a secondary school?” The teachers andstudents appreciated the opportunity for multiple means of expression, inviting the rich literacy experience. As a result of the study, the three participating teachers came to reconsider their instructional agendas to include more multimodal options.